Tectonic Deformation of an Intraplate Orogenic Belt: Mesozoic Sedimentary Basins in the Northeastern Qilian Shan, China - Jia, Jiabao; Zheng, Wenjun; Zhang, Yipeng; Wei, Shiqi; Liang, Shumin; Feng, Changhuan; Zhu, Yu; Tang, Qing; Wang, Weitao (Frontiers in Earth Science, 2022)
The Qilian Shan, located in the northeastern Tibetan Plateau, is an intraplate orogenic belt that underwent several episodes of fold and thrust deformation, particularly during the Mesozoic and Cenozoic. However, the deformation styles and relationships between the basin and mountains remain controversial. Therefore, in the current study, we conducted detailed field mapping of the sedimentary basins in Sunan and Huangcheng, and observed three episodes of compressive tectonic activity. We also restored a deformed section to determine the shortening rate of the Cretaceous sedimentary Sunan Basin. The first thrust episode, during the Paleogene, involved a southwestward thrust motion, comprising the Yumu Shan and Gaizhangdaban thrust systems. The second Neogene episode involved the northeastern thrust belt in the northern Qilian Shan, which comprises the Northern Qilian thrust system. The third episode produced NW-trending strike-slip activity that became the major tectonic deformation style; thus, the entire block rotated clockwise. Additionally, the restored section revealed that the Cretaceous strata have been shortened by ~3.56%. Collectively, these results indicate that the Sunan and Huangcheng area on the northeastern Tibetan Plateau is influenced by the far-field effects of the collision between the Indian and Asian continents, as well as the effects of intraplate orogenic processes related to the collision of the Alashan Block and the Qilian Shan. Therefore, the current study has defined the deformation style in the northeastern Qilian Shan region, so we wish to give a clarification of the tectonic evolution and forecast the tectonic propagation in the Qilian Shan region.